IMPLEMENTING BLENDED LEARNING IN A PRAGMATIC CLASS FOR COLLEGE STUDENTS: WHAT MAKES BLENDED LEARNING ENGAGING? - Daniel Ginting; Yemima Ratih Tegar Putri (Journal of English Educational Study (JEES), 2022)
Looking into blended learning practices in a Pragmatic course attended by the English Letters students, this study aims to investigate the performance of that course based on the point of view of cognitive presence and practical online courses. This study has found that teaching online is a complex phenomenon involving multi-facet aspects. Above all, the students mostly find online learning enjoyable if the facilitators can create a triggering situation; facilitate the learning process; be active in giving comments/feedback to the students, and use multi-learning media to deliver instructions.